IMPLEMENTASI TEORI PERMAINAN PADA STRATEGI PEMASARAN PRODUK KECANTIKAN ORIFLAME DAN JAFRA - Debora Exaudi Sirait (Universitas Islam Sumatera Utara, 2021)
Due to the impact of Covid-19, many Indonesians have been affected by layoffs, so they have switched to taking part in the multi-level marketing program of Oriflame and Jafra products, both of which are the best-selling beauty products today. This study examines the marketing strategy used by these two beauty producers using game theory. Game theory is a theory that uses a mathematical approach in formulating situations of competition and conflict between various interests. This theory was developed to analyze the decision-making process, namely the optimum strategy for different competitive situations and involving two or more interests. The problem boundaries were chosen to be 5 aspects of the problem, namely: product, price, location, promotion, and service. From the results of the preliminary questionnaire reliability test using SPSS 19.0 software, a value of 0.820 was obtained. With a pure strategy, a saddle point is obtained because the maximum value is the same as the minimum value, so that the pure strategy is the optimal strategy. Therefore, with a pure strategy, optimal marketing strategies have been obtained from both manufacturers, namely Jafra and Oriflame. Where Jarfa producers use products (variations) as their marketing strategy while Oriflame producers use price as their marketing strategy.